2015
DOI: 10.1111/aogs.12717
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled study in pregnancy on treatment of marked hyperglycemia that is short of overt diabetes

Abstract: Aiming for normalized glycemia in a pregnancy complicated by severe hyperglycemia reduces fetal growth but is associated with an increased rate of mild hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
0
21
1
Order By: Relevance
“…To reduce rates of negative maternal outcomes and excessive fetal growth as effects of hyperglycaemia in the gestational diabetes group, different treatment strategies need to be evaluated. A recent study regarding treatment of severe hyperglycaemia with a more aggressive treatment, aiming for normoglycaemia, showed a significant reduction on fetal macrosomia . In that study, 67% of women required insulin treatment compared with 36% in the present study.…”
Section: Discussioncontrasting
confidence: 50%
“…To reduce rates of negative maternal outcomes and excessive fetal growth as effects of hyperglycaemia in the gestational diabetes group, different treatment strategies need to be evaluated. A recent study regarding treatment of severe hyperglycaemia with a more aggressive treatment, aiming for normoglycaemia, showed a significant reduction on fetal macrosomia . In that study, 67% of women required insulin treatment compared with 36% in the present study.…”
Section: Discussioncontrasting
confidence: 50%
“…Of 383 citations identified from electronic and hand-searches, we included four unique randomized trials (plus eight companion publications), representing a total of 767 children between 4 and 10 years old (Table 6.1, Figure 6.1). All were randomized controlled trials published in peer-reviewed journals between 1997 and 2015 and conducted in developed countries: Australia 258 , Canada 263 , Sweden 264 , and United States of America. 240 Two trials 258,264 enrolled women with at least one risk factor for GDM, while the other two 240,263 did not select their participants based on GDM risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…A non-randomised retrospective study in the USA found no benefit in outcomes [40] but substantial changes in clinical and obstetric care occurred at the same time [41]. The few randomised trials of treating GDM [12][13][14] have all studied different settings and diagnostic criteria, and a randomised study of the effect on outcomes by treatment on a population level does not exist. Sweden has a public health care system with almost 100% clinical attendance and public health registries with high coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of GDM involves dietary and physical activity advice, blood glucose monitoring, and where necessary metformin or/ and insulin therapy. GDM management has been shown to reduce maternal and perinatal morbidity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%